Innovative approach to the development of conductive hybrid composites for Selective Laser Sintering. (August 2021) - Lupone, Federico; Padovano, Elisa; Ostrovskaya, Oxana; Russo, Alessandro; Badini, Claudio
Graphical abstract: Highlights: Hybrid PA12/carbon fibers/graphite composites were processed through SLS. Evaluation of electrical properties of polymer composites before SLS process. Addition of graphite lowers powders flowability and mechanical properties of parts. Electrically conductive composites were obtained. Abstract: Selective Laser Sintering (SLS) was used to manufacture electrically conductive polymer composites made of polyamide 12 reinforced with carbon fibres and graphite (PA12/CF/GP). Since material design is critical in developing conductive polymer composites, an innovative experimental technique is proposed to preliminary evaluate the electrical behaviour of the powders before SLS processing and select the most performing hybrid compositions. The properties of starting powders and the microstructure, mechanical and electrical behaviour of PA12/CF/GP composites were studied. Results reveal that the addition of graphite lowers the flowability and mechanical properties of the composites compared to the carbon fibres reinforced counterparts. Hybrid composites display great enhancements in the electrical conductivity with respect to the neat PA12 up to anti-static and conductive range; however, no synergistic effect between the two fillers was observed.